-
1) Ask how many days it will take for teams A and B to complete the renovation project of this alley alone.
It will take X days for Team B to complete this project alone.
It takes 5 4 times longer for Team A to complete the project alone than it takes for Team B to complete the project alone, so it takes 5x 4 = days for Team A to complete the project alone.
1/(60/x)+(20/x)=1
80/x=1
x = 80 days for Team A to complete the project alone, and 100 days for Team B to complete the project alone.
2) A total investment of $2 million is invested in this renovation project, if the payment is made according to the amount of work completed, how much will the two teams receive for the project?
The amount of work completed by Team B = 20 x = 20 100 = 1 5 Team B can get the project money = 200 * (1 5) = 400,000 yuan.
Team A can receive project funds = 200-40 = 1.6 million yuan.
-
Because the unit price of A is 2x yuan Yan Jing, the value of the second manuscript is a total of 2000 yuan, so the quantity of A is 1000 x, the same reason because the unit price of B is 3x yuan, so the quantity of B is 1000 x, according to the mixed unit price = total ** divided by the total number to establish the equation: 2000 + 1000 divided by 1000 x + 1000 3x is equal to the unit price is 9, the solution of x = 4, so the unit price of A is 4 times 2 = 8 yuan with jujube filial piety.
-
The key to solving this problem is to see x 2-1 =(x=1)(x-1)6 1-x 2x-5
x^2-1 1-x 1-x
6 1-x+2x-5
i.e. --x 2-1 1-x
6 x-4x+1)(x-1) 1-x
6 4-xx+1)(x-1) x-1
The denominator on both sides is approximated.
-4-xx+1 so (4-x)(x+1)=6
Remove the parentheses and reduce it to x 2-3x+2=0, i.e. (x-1) (x-2) 0 and the ascending key is x=1 or 2
Since x=1 (0 for the de-brightening mother) in the question does not conform to reality, x=2
-
I don't understand. x2-1 if multiplied by 2: The solution is as follows: go and get the denominator of the tong denominator to get 6 (1-x) = (1-x) (2x-1) + (2x-5) (2x-1).
6-6x=2x-1-2xx-x+4xx-2x-10x+5; 2xx-5x-4=0
I'm sorry for the root number, I won't fight. The square of x is xx
-
x-2 x+2 2(x+3)——= ——
x+2 x-2 x-3 denominator, multiply both sides by (x+2)(x-2)(x-3)(x-2) 2*(x-3)+(x+2) 2*(x-3)=2*(x+3)(x+2)(x-2).
Sorted out to 16x=0
The x=0 test is that none of the denominators of the original equation of x=0 is 0, so x=0 is the solution of the original equation.
-
Remove the denominator and multiply both sides by (x+2)(x-2)(x-3)(x-2) 2*(x-3)+(x+2) 2*(x-3)=2*(x+3)(x+2)(x-2).
Sorted out to 16x=0
The x=0 test is that none of the denominators of the original equation of x=0 is 0, so x=0 is the original equation jie
-
Solution: Multiply both sides of the equation by (x+2)(x-2)(x-3) to obtain:
-
One of the solutions is as follows:
Because (3a-2) (2a -a-3) 0 is equivalent to.
3a-2) (a+1)(2a-3) 0, and the zeros of a+1, 3a-2, 2a-3 are -1, 2 3, 3 2, so the set of solutions of the original inequality is.
-
2x(2x+5)-2(2x-5)] (2x-5) (2x+5) =4x 2+6x+10) (4x 2-25)=1
4x 2+6x+10= 4x 2-25, i.e.: 6x=-35
x=-35 auspicious years6
-
Solution: A completes 1 A of the project every day
B completes 1 b of the works every day
B worked for three days and did 3 B
Then A and B did 1 day of work together (1 a+1 b) because the total amount of work was 1
So 3 b + (1 a + 1 b) = 1
You can get the answer you need.
-
By the inscription 1 a+4 b=1
1/a=1-4/b=(b-4)/b
a=b/(b-4)=(b-4+4)/(b-4)a=(b-4)/(b-4)+4/(b-4)a=1+4/(b-4)
First of all, a is an integer.
So 4 (b-4) is an integer.
So b-4 is a divisor of 4.
b-4=1,-1,2,-2,4,-4
a=1+4/(b-4)>=1
So 4 (b-4)>=0
So B-4>0
So b-4 = 1, 2, 4
b=5,6,8
a=5,3,2
So a+b=5+5
a+b=3+6
a+b=2+8
So a+b = 9 or 10
-
From the known 1 a+4 b=1, and because a and b are both natural numbers, a=b=5, that is, a+b=10
-
lz All I know is...
4/b + 1/1 = 1
I can't solve this equation... You can only find the relation between a and b. There is no specific solution.
-
(x-8)(x-8)(x-8)-(x-8)(x-8)(x-8)=(x-8)(x-8)(x-8)-(x-8)(x-8)(x-8)(x-8) and then merge similar terms to obtain (x-8-x+8)(x-8)(x-8)=(x-8)(x-8)(x-8-x+8) -x-8)(x-8)=-(x-8)(x-8) x 8-88x+81=x
-
Multiply both sides by (1-x) (1+x) to get.
2(1+x)+(1-x)(1+x)=x(1-x)
2+2x+1-x^2=x-x^2
Move the item, got. 2x-x 2+x 2-x=-2-1 merge similar terms to obtain.
x=-1 coefficient to one, obtained. x=3
-
The original formula of multiplication (x+1) (x-1) becomes -2 (x+1) = x(x-1), and then I believe you will solve it.
-
Collision hall: set a speed x b speed x x 2 b go Y hours.
Denian collapse: x=10
A: A speed 10km h b speed 12km h
-
A is 10 km h and b is 12 km h
Let the velocity of a be x
30 x=30 Qingling slag (x+2)+
Solve the problem and give up the negative value of Wang Qing, that is, the reputation is quiet.
Fractional equation solution:
1) Remove the denominator. >>>More
Accurately find out the relationship between equal quantities, it is best to lay a good foundation, look at some example problems, and then do it yourself, and then compare your own practice with the work in the book, and do more questions, you will have the feeling of doing problems, and it will be easy to do any problems at that time. >>>More
1)2x+xx+3=1
Multiply both sides of the equation by x(3+3) and remove the denominator. >>>More
1) (x-3 x-2)+1=3 (2-x) solution: (x-3) (x-2)+1=-3 (x-2) The two sides of the equation are multiplied by x-2 to obtain : >>>More
>01-[x/(x^2+1)]^2>0
1+[x/(x^2+1)]}0 >>>More